BENEFITS OF COAL STOCKPILE AT PALIMANAN TO ITS SURROUNDING COMMUNITY - ENDANG SURYATI (Indonesian Mining Journal, 2006)
One of the positive impacts of coal stockpiles in Palimanan is the benefits for surrounding communi- ties. Poling of stockpile developments to people in West Palimanan shows that 81.20 % people agree to have stock pile, 8.57 % disagree and the rest is abstain. Disagreement occurs as the people are afraid with dust pollution from coal stockpiles and transportation.